Respuesta :

Answer:

y = 3

Step-by-step explanation:

    8y - 3 = 16 - (1 -2y)

     8y - 3 = 16 -  1 + 2y             {Subtract 2y from both sides}

8y - 2y - 3 = 16 - 1

      6y -3 = 15           {Add 3 to both side}

       6y = 15 + 3

      6y = 18            {Divide both sides by 6}

       y = 18/6

y = 3

 

Tasyha

Answer:

y = 3

Step-by-step explanation:

[tex]8y - 3 = 16 - (1 - 2y)[/tex]

➡️ [tex]8y - 3 = 16 - 1 + 2y[/tex]

➡️ [tex]8y - 3 = 15 + 2y[/tex]

➡️ [tex]8y - 2y = 15 + 3[/tex]

➡️ [tex]6y = 18[/tex]

➡️ [tex]y = 3[/tex] ✅

ACCESS MORE